The Impact of Social Capital on the Effectiveness of Mobilizing Extrabudgetary Financial Resources for Public General Education in Hochiminh City - Dung, Duong Tri; Phuong, Nguyen Thi Minh; Thanh, Dinh Trung; Nam, Lê Hoai; Tu , Tran Van; Huong, Nguyen Thi; Phuong, Vu Hung (Migration Letters, 2024)
This study aims to examine the impact of social capital on the effectiveness of mobilizing extra-budgetary financial resources for public general education in Ho Chi Minh City. Utilizing quantitative research methods through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM), the research data comprises 458 samples obtained from surveys of managers at various levels in public general education institutions. The findings provide valuable insights, evidencing the intermediary role of perspectives, orientations, and developmental goals, as well as mechanisms in mobilizing financial resources in the relationship between social capital and the effectiveness of financial resource mobilization. Concurrently, the study confirms that social capital positively impacts the subjective perceptions, which in turn positively impact the intrinsic capabilities of schools and the efficiency of financial resource mobilization. Based on these findings, the authors propose several recommendations to enhance the effectiveness of mobilizing extrabudgetary financial resources for public general education in Ho Chi Minh City in the upcoming period.